Regional Differences in Microbial Infiltration of Brain Tissue from Alzheimer’s Disease Patients and Control Individuals - T. Bucky Jones; Ping Chu; Brooke Wilkey; Leigha Lynch; Garilyn Jentarra (Brain Sciences, 2024)
Alzheimer’s disease (AD) is characterized by cognitive decline and neuropathology including amyloid beta (Aβ) plaques and neurofibrillary tangles (tau). Factors initiating or driving these pathologies remain unclear, though microbes have been increasingly implicated. Our data and others’ findings indicate that microbes may be common constituents of the brain. It is notable that Aβ and tau have antimicrobial properties, suggesting a response to microbes in the brain. We used 16S rRNA sequencing to compare major bacterial phyla in post-mortem tissues from individuals exhibiting a range of neuropathology and cognitive status in two brain regions variably affected in AD. Our data indicate that strong regional differences exist, driven in part by the varied presence of Proteobacteria and Firmicutes. We confirmed our data using ELISA of bacterial lipopolysaccharide (LPS) and lipoteichoic acid in the same brain tissue. We identified a potential association between the composition of phyla and the presence of neuropathology but not cognitive status. Declining cognition and increasing pathology correlated closely with serum LPS, but not brain levels of LPS, although brain LPS showed a strong negative correlation with cerebral amyloid angiopathy. Collectively, our data suggest a region-specific heterogeneity of microbial populations in brain tissue potentially associated with neurodegenerative pathology.